Analysis of the Effects of Education Level, Minimum Wage, and Migration on Unemployment in West Java - Salsabilla, Amelia; Pratomo, Devanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
West Java Province is one of the provinces with the largest population in Indonesia. However, the poverty rate is quite high and even ranked first in all of Java in the 2019-2023 period. For this reason, it is necessary to find a solution to overcome the problem of poverty. This study aims to determine the effect of education level, minimum wage and migration on the poverty rate in West Java Province in 2019-2023. The data used are secondary data from the poverty rate, education level, minimum wage and migration in cities/regencies in West Java Province for the 2019-2023 period obtained from the BPS of West Java Province. The data analysis method used is panel data regression. The results of the study show that education and migration have a negative and significant effect on poverty in West Java, the minimum wage has a positive and significant effect on poverty in West Java